2011
DOI: 10.1038/modpathol.2010.195
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein LIN28 is a marker for primary extragonadal germ cell tumors: an immunohistochemical study of 131 cases

Abstract: LIN28 has been shown to have an important role in primordial germ cell development and malignant transformation of germ cells in mouse. In this study, we examined the immunohistochemical profile of LIN28 in 131 primary human extragonadal germ cell tumors (central nervous system (CNS) 76, mediastinum 17, sacrococcygeal region 30, pelvis 3, vagina 2, liver 1, omentum 1, and retroperitoneum 1), including the following tumors and/or components: 57 seminomas/germinomas, 10 embryonal carcinomas, 74 yolk sac tumors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…LIN28 is a highly sensitive and relatively specific cytoplasmic marker for primary extragonadal and testicular germ cell tumors, including intratubular germ cell neoplasias, seminomas, yolk sac tumors, and embryonal carcinomas. 114,115 The utility of LIN28 is similar to that of SALL4.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…LIN28 is a highly sensitive and relatively specific cytoplasmic marker for primary extragonadal and testicular germ cell tumors, including intratubular germ cell neoplasias, seminomas, yolk sac tumors, and embryonal carcinomas. 114,115 The utility of LIN28 is similar to that of SALL4.…”
mentioning
confidence: 56%
“…1,112,113 SALL4 and lin-28 homolog A (LIN28) are highly sensitive and specific markers for identifying a tumor of germ cell origin. [88][89][90][91][92][93][94][95]114,115 The markers for determinining many neoplasms are summarized in Table 3.…”
Section: Determination Of a Broad Category Of Neoplasmmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the expression of LIN28A/LIN28B is highly restricted to ES cells and developing tissues, and expression dramatically decreases as differentiation progresses (2,3,7,8,11,21,40,41). In human tumors, LIN28A/LIN28B expression is up-regulated/reactivated (4,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51) and may function as an oncogene promoting malignant transformation (42,43,52,53), inducing metastasis (43,46,(52)(53)(54), regulating inflammation (5,43), and maintaining the cancer stem cells (43,45,(55)(56)(57). Clinical studies have indicated that higher levels of LIN28A/LIN28B expression are associated with poor clinical outcomes (44,58,59) and that LIN28 family polymorphisms may influence susceptibility to ovarian (60) and breast (61) cancers.…”
mentioning
confidence: 96%
“…The above-mentioned studies provided a range of markers that have been validated for the identification of GCNIS and seminoma/(dys)germinoma in tissue specimens by immunohistochemistry, including OCT4 [36,39,49,50], NANOG [51,52], LIN28 [47,53], AP-2γ [54][55][56], podoplanin (PDPN, M2A, D2-40, Aggrus) [57,58], and KIT [33]. The markers that are useful in clinical practice and research are listed in Table 1.…”
Section: Immunohistochemical Markers Useful For Gct Diagnosis In Tissmentioning
confidence: 99%